PKM FOR TEACHERS IN THE WOLTERMONGINSIDI’S GUGUS, KALIWUNGU DISTRICT, KENDAL TO BECOME SKILLED IN MAKING ARTIFICIAL INTELLIGENCE-BASED MEDIA WITH GUIDED GUIDANCE - Choirul Huda; Kartinah Kartinah; Aries Tika Damayani; Husni Wahyudin (SWAGATI : Journal of Community Service, 2026)
One of the demands of education stakeholders in the current era is to produce quality graduates who are technologically savvy. Therefore, achieving quality graduates requires continuous improvement in the quality of learning in schools. One way to improve the quality of classroom learning is by improving teacher competency. There are many teacher competencies that need to be improved related to classroom learning, one of which is by creating learning using creative and innovative learning media. The ability of elementary school teachers in Kaliwungu District, Kendal Regency, especially in the Wolter Monginsidi Cluster, in using learning media requires teachers to be equipped with the knowledge and skills to create AI-based elementary school learning media. The results obtained from this community service activity were that 90% of participants were able to create AI-based learning media that can be used by students in their classes. Based on what happened during the workshop and the positive results, it can be concluded that similar activities can be repeated in other Clusters with a wider variety of AI-based learning media